Construction of Circular RNA–MicroRNA–Messenger RNA Regulatory Network of Recurrent Implantation Failure to Explore Its Potential Pathogenesis - Luo, Jiahuan; Zhu, Li; Zhou, Ning; Zhang, Yuanyuan; Zhang, Lirong; Zhang, Ruopeng (Frontiers in Genetics, 2021)
Abstract Background Many studies on circular RNAs (circRNAs) have recently been published. However, the function of circRNAs in RIF is unknown and remains to be explored. This study aims to determine the regulatory mechanisms of circRNAs in RIF. Methods Microarray data of RIF circRNA (GSE147442), miRNA (GSE71332) and mRNA (GSE103465) were downloaded from Gene Expression Omnibus (GEO) database to identify differentially expressed circRNA, miRNA and mRNA. The circRNA-miRNA-mRNA network was constructed by cytoscope 3.8.0 software, then the protein-protein interaction (PPI) network was constructed by STRING database, and the hub genes were identified by cytohubb plug-in. The circRNA-miRNA-hubgene regulatory subnetwork was formed to understand the regulatory axis of hub genes in RIF. Finally, the Gene Ontology (GO) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis of the hub genes were performed by ClusterProfiler package of Rstudio software, and Reactome FI plug-in was used for reactome analysis to comprehensively analyze the mechanism of hub genes in RIF. Results A total of 8 upregulated differentially expressed circRNAs (DECs), 5 downregulated DECs, 56 downregulated differentially expressed miRNAs (DEmiRs), 104 upregulated DEmiRs, 429 upregulated differentially expressed mRNAs (DEGs) and 1067 downregulated DEGs were identified regarding RIF. The miRNA response elements of 13 DECs were then predicted. 7 overlapping miRNAs were obtained by intersecting the predicted miRNA and DEmiRs. Then, 56 overlapping mRNAs were obtained by intersecting the predicted target mRNAs of 7 miRNAs with 1496 DEGs. The circRNA-miRNA-mRNA network and protein-protein interaction network (PPI) were constructed through 6 circRNA, 7 miRNA and 56 mRNA, and four hub genes (YWHAZ, JAK2, MYH9 and RAP2C) were identified. The circRNA-miRNA-hub gene regulatory subnetwork with 9 regulatory axis was formed in RIF. Functional enrichment analysis and reactome analysis showed that these four hub genes were closely related to the biological functions and pathways of RIF. Conclusion The results of this study provide further understanding of the potential pathogenesis from the perspective of circRNA-related competitive endogenous RNA network in RIF.